2008
DOI: 10.1021/ja803999r
|View full text |Cite
|
Sign up to set email alerts
|

Binary and Gray-Scale Patterning of Chemical Functionality on Polymer Films

Abstract: We present a facile technique for the gray-scale chemical functionalization of polymer surfaces with high dynamic range. We demonstrate the use of this technique to create amine-functionalized substrates that are used for the patterned binding of fluorophores and the patterned synthesis of peptides. Studies of the behavior of the model organism Dictyostelium discoideum indicate the biocompatibility of the functionalized substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…We functionalized the nanoridges with collagen IV to render the surfaces adherent to mammalian cells such as MCF10A human breast epithelial cells and HL60 neutrophil-like cells. The exposed amine groups on collagen react naturally with surface acrylate groups through Michael addition 29 . To characterize the collagen coating, we treated the collagen-IV-coated nanoridges with NHS Alexa 594, which fluorescently labels the protein but not the acrylic polymer (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We functionalized the nanoridges with collagen IV to render the surfaces adherent to mammalian cells such as MCF10A human breast epithelial cells and HL60 neutrophil-like cells. The exposed amine groups on collagen react naturally with surface acrylate groups through Michael addition 29 . To characterize the collagen coating, we treated the collagen-IV-coated nanoridges with NHS Alexa 594, which fluorescently labels the protein but not the acrylic polymer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Any protein/peptide with surface amine and/or thiol groups is expected to exhibit good adhesion. The curing time of the replica can also be tuned to adjust the density of residual acrylate groups on the polymer surface available for the subsequent protein coating 29 .
Figure 4 Functionalization of nanoridges with collagen IV.
…”
Section: Resultsmentioning
confidence: 99%
“…30 While Dictyostelium is commonly studied migrating on glass, we have previously shown that it migrates with equal speed on acrylic surfaces. 32 …”
Section: Resultsmentioning
confidence: 99%
“…The monomers tris (2‐hydroxy ethyl) isocyanurate triacrylate (SR368 – Sartomer ® ) and dipentaerythritol pentaacrylate (SR399 – Sartomer ® ) were mixed in a proportion of 10/90 wt%. This prepolymer resin has been used previously, with some differences in the monomers proportion, for photonic and biological applications . Ethanol (2 mL) was added to the monomer composition to assist their dissolution.…”
Section: Methodsmentioning
confidence: 99%